Hypokalemic Periodic Paralysis Precipitated by Thyrotoxicosis and Renal Tubular Acidosis - Ian Jackson; Yazan Addasi; Moeed Ahmed; Bashar Ramadan; Karson Kalian; Noor Addasi; Ali Nayfeh; Jocelyn Taylor; Khalid Bashir; Bryan Krajicek (Case Reports in Endocrinology)
Background. Hypokalemic periodic paralysis is a rare neuromuscular disorder characterized by transient episodes of flaccid paralysis due to a defect in muscle ion channels. Most cases are hereditary, but it can be acquired. We present a case of acquired hypokalemic periodic paralysis associated with hyperthyroidism and renal tubular acidosis. Clinical Case. A 38-year-old female with a history of Graves’ disease presented to the emergency department with generalized weakness and associated nausea, vomiting, and weight loss. Examination was significant for diffuse weakness in all extremities. Labs showed hypokalemia, hyperthyroidism, and nonanion gap metabolic acidosis with a positive urine anion gap. She was treated for hypokalemic periodic paralysis and renal tubular acidosis. Potassium replacement, propranolol, methimazole, and sodium bicarbonate were initiated. Her potassium gradually corrected with resolution of her symptoms. Further investigation revealed a history of dry eyes, dry mouth, and recurrent dental carries. She had positive ANA, SS-A, and SS-B antibodies. She was diagnosed with Sjögren’s syndrome, which may have been associated with her Graves’ disease and thus contributed to both her RTA and hyperthyroidism. Conclusion. Early recognition and treatment of thyrotoxic periodic paralysis are important to prevent cardiac complications. Management includes potassium replacement with careful monitoring to prevent rebound hyperkalemia. The definitive treatment is to achieve euthyroid status.